Pengembangan Koleksi Perpustakaan di Perpustakaan Kopertis Wilayah X - Wahyuni, Sri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper discusses the Library Collection Development in Libraries Kopertis Region X. The purpose of writing this paper are (1) to describe the development process is done in the library collection Kopertis Region X, and (2) to describe the kind of collection that was developed at the Library Kopertis Region X. Data collection in the study through the method of observation and interviews. Based on the data it can be concluded peganalisisan first, the development process is done in the library collection Kopertis Region X is still a selection of library materials and library provision. Second, the collection type that was developed at the Library Kopertis Region X is still a work print as umun collection, a collection of reference (encyclopedias, dictionaries, handbooks, and directories), a collection of periodicals (magazines, journals and tabloids), and government publications kolesi (law the set of state laws and regulations). While there in the form of printed works separti CDs, and tapes. It was contained in a particular book. Keywords: library collection; collection development